Pengaruh Tingkat Edukasi dan Spesialisasi Pendidikan CEO terhadap Performa Perusahaan di Indonesia - Kevin Wiyarta Erlim; Rita Juliana (Universitas Kristen Maranatha, 2017)
Using sample of non financial Indonesia public licted firms over the period from 2005-2014, we analyze the impact of CEO education level education specialization on firm performance. Globalization has a lot of impact on professionals’ careers and thus it will affect the qualification that a CEO needed. We believe that education level and CEO education specialization will affect the managerial decision making process and their strategy. This study is using panel data with fixed effect model methodology. We also did classic assumption test such as autocorrelation test, heteroscedasticity test and cross-sectional dependence test. Our analysis results that CEO education level does have impact on firm performance, and should be considered as an important aspect of a CEO. Keywords: CEO Education Level; CEO Education Specialization; Fixed Effect Model; Firm Performance; TobinsQ